Selection the type of investment in Malaysia using Fuzzy Analytic Hierarchy Process (AHP) / Ardini Athirah Mhd Munawar and Mohd Fazril Izhar Mohd Idris - Mhd Munawar, Ardini Athirah; Mohd Idris, Mohd Fazril Izhar (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Everyone has their own preference and unique choice of investment based on their desire, needs and goals. But nowadays, in the present day of the financial market, investment has become complicated especially for youth because there is a lack of knowledge about investment. Thus, this study is to choose the best type of investment by using Fuzzy Analytical Hierarchy Process. Besides that, the process to achieve the main objective of this study is to study the criteria for selecting the best type of investment and to rank the merit of criteria and alternatives by using Fuzzy Analytical Hierarchy Process. This study is using the Fuzzy Analytical Hierarchy Process method to determine the degree of uncertainty when converting human preferences into a score based on various selection criteria in investment. Based on the result shows that gold is the best investment for the investor to invest their assets at the moment.